2016
DOI: 10.1159/000448350
|View full text |Cite
|
Sign up to set email alerts
|

Aging, Cognitive Decline and Hearing Loss: Effects of Auditory Rehabilitation and Training with Hearing Aids and Cochlear Implants on Cognitive Function and Depression among Older Adults

Abstract: A growing interest in cognitive effects associated with speech and hearing processes is spreading throughout the scientific community essentially guided by evidence that central and peripheral hearing loss is associated with cognitive decline. For the present research, 125 participants older than 65 years of age (105 with hearing impairment and 20 with normal hearing) were enrolled, divided into 6 groups according to their degree of hearing loss and assessed to determine the effects of the treatment applied. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
158
4
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(175 citation statements)
references
References 38 publications
3
158
4
10
Order By: Relevance
“…In our study, more than half of participants with MCI had the amnestic subtype, suggesting that type of MCI does not account for the low rate of progression. A combined effect of improvement in speech perception and cognitive training, the latter being an integral part of speech therapy, could account for the improvement in cognitive abilities observed in short-term studies [14][15][16][17] . Regarding the statistically significant decline in several cognitive test scores after 1 year, the extent of the changes was mild and consistent with that observed in aging individuals, and speech therapy have no influence on these scores.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, more than half of participants with MCI had the amnestic subtype, suggesting that type of MCI does not account for the low rate of progression. A combined effect of improvement in speech perception and cognitive training, the latter being an integral part of speech therapy, could account for the improvement in cognitive abilities observed in short-term studies [14][15][16][17] . Regarding the statistically significant decline in several cognitive test scores after 1 year, the extent of the changes was mild and consistent with that observed in aging individuals, and speech therapy have no influence on these scores.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies has suggested the adverse effects of hearing impairments on depression and cognition, especially in the elderly [31,32]. In addition, strong correlations of depression and anxiety with self-reported hearing loss have been reported [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Naturalistic assessments of neuropsychiatric status before and after hearing treatment have shown improvement on short-and long-term global cognition, memory tasks, depressive symptom scores, and social functioning (7375). An open series of 40 older adults assessed before and after hearing aid fitting showed a significant decline in reported loneliness after 4–6 weeks of hearing aid use; patients with more severe hearing loss reported the greatest improvements (76).…”
Section: Treating Hearing Impairment To Prevent or Reverse Adverse Nementioning
confidence: 99%